1980
DOI: 10.1111/j.1476-5381.1980.tb10922.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Prostanoid‐induced Contractions of Rat Gastric Fundus Muscle by Sc‐19220, Sodium Meclofenamate, Indomethacin or Trimethoquinol

Abstract: 3 The effect of the cyclo-oxygenase inhibitor sodium meclofenamate, 1 or 2 1tg/ml, on 6,15-diketo-PGFl, or thromboxane B2 was similar to the small antagonism of ACh, whereas the other prostanoids were blocked to greater extents. Indomethacin, 1 jig/ml, also reduced contractions to the prostanoids, but antagonism of the PGH2 epoxymethano analogues was considerably less than with meclofenamate. 4 The ,B-adrenoceptor stimulant trimethoquinol, 50 ng/ml, was the most potent prostanoid antagonist tested; all the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…adminIstered PGDz• In agreement with the present findings an antagonism of the effects of exogenous prostaglandins by fenarnates and indomethacin has been reported in several tissues: Sodium meclofenamate and other fe~amate7 antagonise th: effects of exogenous prostaglandins in rat, gumea-plg and human allJl'entary muscle (11,12), human bronchial nruscle (20)! an~ these drugs attenuate the PGF 2 a-induced bradycardia and hypoenslon ln the cat· (21) and prostaglandin-induced gastric acid secretion ill the rat (22).…”
Section: Effects Of Indomethacin and Sodium Meclofenamatesupporting
confidence: 90%
See 2 more Smart Citations
“…adminIstered PGDz• In agreement with the present findings an antagonism of the effects of exogenous prostaglandins by fenarnates and indomethacin has been reported in several tissues: Sodium meclofenamate and other fe~amate7 antagonise th: effects of exogenous prostaglandins in rat, gumea-plg and human allJl'entary muscle (11,12), human bronchial nruscle (20)! an~ these drugs attenuate the PGF 2 a-induced bradycardia and hypoenslon ln the cat· (21) and prostaglandin-induced gastric acid secretion ill the rat (22).…”
Section: Effects Of Indomethacin and Sodium Meclofenamatesupporting
confidence: 90%
“…Furthenoore, the central hypotensive effect of PGI 2 was antagonised by sodium meclofenamate (13). Indomethacin has been repqrted to blunt the PGDz-induced contractions of the longitudinal nruscle of rat gastric fundus (12) and to reduce submaximal contractions to PGE 1 in gerbil colon (23). Antagonism of the prostaglandin action by indumethacin has also been demonstrated in rat uterus (24) and in isolated guinea-pig ileum and rabbit ear preparations (25).…”
Section: Effects Of Indomethacin and Sodium Meclofenamatementioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the EP 1 receptor antagonist SC19220 caused a statistically significant inhibition of contraction to both iloprost and beraprost. These data are consistent with the findings of Bennett et al (1980). DBTSA may also antagonize TP and DP receptors at the concentration used in this study (Gallant et al, 2002).…”
Section: Selexipag and Gastric Function 253supporting
confidence: 82%
“…gastric fundus as evidenced by contraction to the EP 3 /EP 1 receptor agonist sulprostone (Bennett et al, 1980). Furthermore, contraction of rat fundal strips (Dong et al, 1986) and guinea pig ileum (Lawrence et al, 1992) to PGI 2 analogs has been reported.…”
Section: Introductionmentioning
confidence: 99%